Strategi diferensiasi, orientasi pasar dan persepsi harga terhadap keunggulan bersaing Marketplace Shopeefood - Yucha , Nikma; Cahyani, Ida Putri Nur (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to analyze whether the differentiation strategy, market orientation, price perception on competitive advantage in the ShopeeFood marketplace at Maarif Hasyim Latif University students. In this study using quantitative research methods. This research was conducted on students of Maarif Hasyim Latif University, Faculty of Economics with a population of 541 students. The sampling technique of this research uses purposive sampling. The study uses multiple linear regression data analysis techniques. The results of this study show, the differentiation strategy partially has a positive and insignificant effect on competitive advantage, market orientation partially has a positive and significant effect on competitive advantage, price perception has a positive and significant effect on competitive advantage, differentiation strategy, market orientation, and price perception simultaneously have a positive and significant effect on competitive advantage. The implications this research it is hoped that ShopeeFood will pay more attention to the factors affect its competitive advantage. This allows ShopeeFood to implement the right strategy to maximize profit growth.